Characterising the force balance between active pharmaceutical ingredients for inhalation and its impact on deposition - Piggott, Matthew John (2013)
Interparticulate interactions play a significant role in determining the downstream behaviours of all pharmaceutical formulations and are therefore essential considerations when approaching formulation design. Inhalation product formulation in particular is inherently bound to an understanding of these forces. Delivery of drugs to the lower airways to treat conditions like asthma and COPD requires a particle size of below 5 micron. This implicitly demands micronization of the active pharmaceutical ingredients (APls) and this process renders many particles of large surface area with high surface energies and an auto-adhesive tendency. There is therefore a concurrent reduction in the flowability and dispersion properties of these systems. The interactive character predisposes agglomeration, flocculation or device retention and will compromise manufacture, stability, device function, and the aerosolization behavior of a formulation. Ultimately the ability of any aerosolized API to reach the deep airways is dependent upon adhesion force dynamics. As such, an appreciation of the forces of attraction and scale of particulate interactions within inhaler technology is critical if a successful drug delivery device is to be realized. The advancement of the atomic force microscope (AFM) as a force probing apparatus, has meant that it is now possible to measure the force of adhesion between two particles of interest. However these measurements could not easily be compared, because there is no simple means to account for differences in the contact regime (geometrics) between measurements. However, the development of the cohesive adhesive balance (CAB) approach by Begat, Morton, Stainforth and Price in 2004 has offered a means to negate this limitation. Using a colloidal probe microscopy (CPM) derived technique a particle of a selected material of interest (API, carrier molecule etc.) is attached to an AFM cantilever and ramped onto and off the surface of another material of interest (adhesion measurement), and to a surface of the same material as the tip (cohesion measurement). By graphically plotting the adhesive force values of a series of tips, as a function of the cohesive force values of the same tips, a representation of the relative particle interaction can be obtained. Quantitative information regarding the adhesive/cohesive nature of the interaction can then be extracted from the graph and a description of the interaction formulated that can be compared to other material combinations. The CAB work carried out to date has used recrystallized model substrates. These molecularly flat surfaces ensured there would be no difference between the contact geometry of a functionalised AFM probe and the adhesive and cohesive surfaces of the study respectively. In this fashion the only variable between the two measurements would be the chemical interactivity, and not the interactive surface area. However while using such methodology guarantees the validity of the approach, it is not necessarily a true representation of the materials 'in-situ' and requires more complex sample preparation and complex experimental design. For a variety of reasons this can be misleading in its own right. This thesis details the .investigation into the application of an adapted CAB approach in characterizing the force balance between APls for inhalation in their real state. In so doing, the aim was to see whether such a CAB would offer a quicker and simpler, yet relevant and informative assessment of a drug system force balance. It was hoped that said force balance could in turn be associated with a measurable impact upon the formulation performance of the characterised ingredients as measured 'in-vitro'. This interest was particularly directed at the lesser characterized pressurized metered dose inhaler (pMOI) systems. While these formulations are solvent based, it was of interest to identify whether a simple API to API challenge could infer a descriptive balance that could link to 'in-vitro' performance. Furthermore there was interest in evaluating the use of a range of surface specific imaging techniques to analyse the deposition dynamics of the combination formulations. It was hoped that by doing so, the localisation of the individual components within the binary deposits could again be associated back to the force balance of that system, and that an appreciation of the capability of the techniques involved would be gained. The work that follows therefore commences with the evaluation and description of the capacity for the CAB approach to be adapted to measure force relationships between real beclomethasone dipropionate (BOP) particles and pMDI component surfaces. From this assessment it was found that even with relatively smooth substrates, the combination of bulky functional particles and the inherent substrate roughness caused a critical failure in the CAB model. The parity between cohesive and adhesive geometries of contact was excessively stretched, leading to a loss of force normalisation which was reflected in uncorrelated CAB plots. As a consequence little could be confidently gleaned from the force data acquired, although there was the suggestion that the use of a fluorinated ethylene proplylene (FEP) coating reduced the adhesive interaction between the APls and the pMDI canister wall. This was then followed by an attempt to find a compromise between the model crystal substrates of a pure CAB process and the real particle morphologies that had caused the CAB model to fail. Using a compression process to form API powder compacts, in conjunction with small and discreet functional particles, a confident CAB was achieved for two combinations of APls selected on the basis of surface energy and physical stability analysis. Salbutamol sulphate was characterised with beclomethasone dipropionate, and salmeterol xinafoate with fluticasone propionate. Both combinations showed CAB plots with a sufficiently strong linear regression analysis to suggest a broad accuracy of force balance assessment. Both beta2-agonists showed cohesively dominated relationships with respect to the paired glucocortiocoids, while in reverse both glucocorticoids showed adhesively dominated relationships with the beta2-agonists. There was concern raised over the compression process of the powder discs, and its impact on the physicochemical state of the APls, with some thermodynamic evidence of polymorphic changes that required further work. The next chapter looks at the 'in-vitro' deposition performance of the two API combinations from a HFA134a pMDI system by analysis in an Andersen Cascade Impactor (ACI). The coformulation of salmeterol with fluticasone induced an improvement in the fine particle performance of fluticasone, with a concurrent decrease in the fine particle performance of salmeterol. This impact was hypothesised to be related to alterations in the structure and strength of particle-particle agglomerates. The impact on deposition performance of coformulating beclomethasone and salbutamol was unclear, as a critical unexplained loss of beclomethasone by total recovered mass was seen from all beclomethasone containing formulations. This instability of beclomethasone within the HFA134a system, precluded an accurate assessment of a direct impact on salbutamol deposition. The final chapter, compared a range of surface specific imaging techniques, including scanning electron microscopy (SEM), desorption electrospray ionization mass spectrometry (DESI), Raman spectrometry and time-of-flight secondary ion mass spectrometry (ToF-SIMS) in assessing the extent and nature of 'in-vitro' co-deposition from the salmeterol and fluticasone pMDI formulations. It was apparent that the deposition of the two APls on ACI plates was not likely to be directly comparable assessment of the incidence of particle co-deposition 'in-vivo' due to the forced nature of nozzle directed impaction. However the combination of techniques employed produced a wealth of physical and chemical data that did suggest that the two APls showed extensive co-ordination 'in-vitro'. Raman spectroscopy was able to identify individual particle character and showed frequent salmeterol and fluticasone particle combinations, but suffered from exceptionally long run times and anomalies from photoreactive surface elements. The use of a multivariate approach to ToF-SIMs analysis defined the strong co-association of the two APls, although could not differentiate particle to particle deposition. Multivariate curve resolution (MeR) was used and produced distinct components that segregated ions from both APIS from the background plate but not from each other. SEM imaging was able to define the morphologies of the deposited particles, but was unable to differentiate the two. DES I imaging showed the presence of the two APls together within several drug spots, but could not be used to investigate individual drug spots, and the distribution within, due to inadequate spatial resolution and differences in desorption efficacy. While the co-association of the two APls was observed, the lack of a comparator in another combination of APls made the link between deposition performance and force balance purely descriptive. It was unclear as to whether the force balance of the system lends itself to a particular increase in co-deposition behaviour. However it was apparent that the analytical techniques employed all had respective strengths and weaknesses as mapping tools, and with further work with other formulations could be used to provide a tailored formulation screening process, if subsequent links to force balances could be made. To conclude, the work in this thesis details the successful process of adapting an AFM technique in characterising the broad force balance of combinations of APls. In so doing a force balance has been linked to the alteration in deposition behaviour of two APls when co-formulated in a HFA134 formulation. The subsequent co-deposition of the two APls was then analysed by a series of surface analytical techniques. This highlighted a general co-deposition trend, but the collective results were unable to definitively link to the force balance of the system. The information obtained forms the beginnings of what could be utilised as a fast and facile broad predictor of pMDI formulation performance, and an indication of appropriate analytical techniques for investigating particle association 'in-vitro'.